1912
DOI: 10.1152/ajplegacy.1912.31.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Action of the Thromboplastic (Zymoplastic) Substance of the Tissues

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

1943
1943
1969
1969

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…The papers were removed after the front had ascended about 40 cm., which took two to three hours. Before staining, the pa- 3 Part No. C-4249-2X, Scientific Glass Co., Bloomfield, N. J.…”
Section: Methodsmentioning
confidence: 99%
“…The papers were removed after the front had ascended about 40 cm., which took two to three hours. Before staining, the pa- 3 Part No. C-4249-2X, Scientific Glass Co., Bloomfield, N. J.…”
Section: Methodsmentioning
confidence: 99%
“…It is now known that this is due to a specific interaction between the tissue extracts (tissue factor) and a plasma protein, factor VII (1, 2). Although the structure of tissue factor is not known, it has been clear for many years that it contains both a protein and lipid moiety (3). In a previous study on the lipid component of tissue factor, it was demonstrated that certain phospholipids were necessary for full biological activity to be achieved (4).…”
Section: Introductionmentioning
confidence: 99%
“…The crude cephalin of Howell accelerated clotting (2), whereas the extraction of lipid from plasma by Macfarlane, Trevan and Attwood inhibited its coagulation (3). Many studies have stressed the role of phospholipids in coagulation.…”
mentioning
confidence: 99%